1987
DOI: 10.1128/iai.55.7.1668-1673.1987
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin neutralization with rabbit antisera to Escherichia coli J5 and other gram-negative bacteria

Abstract: To study the mechanisms of protection against endotoxin challenge offered by antisera to smooth and rough gram-negative organisms, we have developed an assay to quantitate endotoxin neutralization based on inhibition of the Limulus amoebocyte lysate test. Dilutions of different bacterial lipopolysaccharides (LPSs) were incubated with hyperimmune rabbit sera against Escherichia coli 0113, E. coli 018, and rough mutants E. coli J5 and Salmonella minnesota Re595 and were then combined with limulus lysate. The gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 33 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…None of the antibody isotypes in J5 hyperimmune sera had marked cross reactivity with purified LPS or lipid A in ELISA ( Figures 5 to 7). In other studies, antibodies elicited in rabbits with fewer immunizations also showed little cross reactivity with LPS or lipid A (Siber et al, 1985;Warren et al, 1987;Hellman et al, 1997). Core antigens are suggested to be important inducers of protective antibodies in J5-immunized animals (Baumgartner et al, 1987;Pollack et al, 1989;Aydintug et al, 1989;Tyler et al, 1991Tyler et al, , 1992.…”
Section: Discussionmentioning
confidence: 82%
“…None of the antibody isotypes in J5 hyperimmune sera had marked cross reactivity with purified LPS or lipid A in ELISA ( Figures 5 to 7). In other studies, antibodies elicited in rabbits with fewer immunizations also showed little cross reactivity with LPS or lipid A (Siber et al, 1985;Warren et al, 1987;Hellman et al, 1997). Core antigens are suggested to be important inducers of protective antibodies in J5-immunized animals (Baumgartner et al, 1987;Pollack et al, 1989;Aydintug et al, 1989;Tyler et al, 1991Tyler et al, , 1992.…”
Section: Discussionmentioning
confidence: 82%
“…E. coli J96, IA2 and H5 are smooth-strain uropathogenic clinical isolates kindly maintained and provided by Dr J. R. Johnson (Department of Medicine, University of Minnesota, MN, U.S.A.) and described in Johnson and Brown [26] for J96 and IA2 and in Johnson and Brown [27] for H5. J5 is an E. coli rough strain initially referenced by G. R. Siber and discussed in Warren et al [28] and is analogous to the smooth-strain E. coli 0111 :B4 used in the BioWhittaker Limulus amoebocyte lysate (LAL) endotoxin detection and quantification kit described below. Gram-positive MN8 and MNHO are two patient isolates of S. aureus, which were kindly provided by Professor P. M. Schlievert (Department of Microbiology, University of Minnesota, MN, U.S.A.) and described in Bohach et al [29] for MNHO and in Schlievert and Blomster [30] for MN8.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Second, administration of LPS alone to experimental animals reproduces the EC injury seen after gram-negative bacterial challenge (13,26). Lastly, in some animal studies, interventions that specifically target the LPS molecule appear to protect against the EC complications associated with gram-negative sepsis or experimental LPS challenge (1,33,34). The efficacy of most of these interventions has yet to be evaluated in humans.…”
mentioning
confidence: 99%
“…The LPS-binding site is 32 to 50 amino acids in length and forms an amphipathic loop which binds to the lipid A portion of LPS (18,24,32). ENP or LALF neutralizes LPS bioactivity in the Limulus amebocyte lysate assay (11,32), prevents macrophage production of tumor necrosis factor in vitro (4), and protects against LPS challenge in vivo (11,33).…”
mentioning
confidence: 99%